Identifikasi Peran Gender Perempuan Pemecah Batu di Kelurahan Temu, Kabupaten Sumba Timur, Nusa Tenggara Timur - Hura, Teddy Berkham Kalendi Laki; Nugrohowardhani, Rambu Luba Kata Respati (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2024)
The purpose of this study is to examine the gender roles of women engaged in stone breaking in Kelurahan Temu, East Sumba Regency, East Nusa Tenggara Province. This research seeks to understand the gender roles of female stone breakers through the lens of gender role theory, which distinguishes between domestic and public roles, as well as theory on women's roles categorized into reproduction, production, and social interactions. Utilizing qualitative research methods, data were collected through observations, in-depth interviews, and documentation. Informants were purposefully selected based on specific criteria. The collected data underwent qualitative analysis, compared with existing research findings, leading to conclusive insights.The findings highlight that female stone breakers in Kelurahan Temu actively perform their roles as homemakers, laborers, and participants in both domestic and public spheres. Therefore, it is evident that these women effectively carry out various gender roles, including reproductive, productive, and social roles, in accordance with community norms and expectations.